2022
DOI: 10.1186/s13568-022-01436-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of ambr®250 to assess mucic acid production in fed-batch cultures of a marine Trichoderma sp. D-221704

Abstract: Mucic acid, a diacid with potential use in the food, cosmetic, chemical and pharmaceutical industries, can be produced by microbial conversion of D-galacturonic acid, which is abundant in pectin. Using the ambr®250 bioreactor system, we found that a recently generated transformant (D-221704, formerly referred to as T2) of a marine Trichoderma species produced up to 53 g L−1 mucic acid in glucose-limited fed-batch culture with D-galacturonic acid in the feed at pH 4, with a yield of 0.99 g mucic acid per g D-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some first application studies can be found, e.g. by Tamminen et al using the Ambr 250 [15,16], Jansen et al using the BioLector [14,17,18] and Bendig and Weuster-Botz using the bioREACTOR 48 [19]. However, these methods are not yet widely employed with filamentous fungi.…”
Section: Fungal Strain and Bioprocess Development: Small-scale Cultiv...mentioning
confidence: 99%
“…Some first application studies can be found, e.g. by Tamminen et al using the Ambr 250 [15,16], Jansen et al using the BioLector [14,17,18] and Bendig and Weuster-Botz using the bioREACTOR 48 [19]. However, these methods are not yet widely employed with filamentous fungi.…”
Section: Fungal Strain and Bioprocess Development: Small-scale Cultiv...mentioning
confidence: 99%